Does the Eyebrow Sag with Aging? An Anthopometric Study of 95 Caucasians from 20 to 79 Years of Age. Issue 2 (February 2016) - Bruneau, Stéphane; Foletti, Jean-Marc; Muller, Samuel; Vercasson, Camille; Lauwers, Frederic; Guyot, Laurent
Abstract : Background: It is commonly assumed that a progressive sagging of the eyebrow occurs with the facial aging process. Only a few studies have analyzed this modification, and the findings are disparate and inconclusive. This study, based on reproducible and validated data, aimed to quantify the modifications of eyebrow position that may occur with aging. Also analyzed were the effects of these eyebrow position changes on the upper eyelid and on frontal muscle activity. Methods: The study included 95 Caucasian adults divided in three groups: 20 to 39, 40 to 59, and 60 to 79 years of age. Photographic portraits were made using a standardized photograph protocol. Eyebrow position was evaluated from the intercanthal line to four points along the upper margin of the eyebrow. The upper eyelid height, the lid sulcus height, and the upper iris coverage were measured. Severity of the forehead lines was analyzed using a validated scale. Reliability and validity of all measures were controlled beforehand. Results: No significant differences were found when comparing eyebrow height above the medial canthus, the pupil, the lateral sclero-corneal limbus, and the lateral canthus between groups ( p > 0.5). In addition, results suggested an increase of dermatochalasis when eyebrow height decreased. Also demonstrated was a significant increase of frontal muscle activity with aging. Conclusions: In contrast to conventional descriptions, this study demonstrated the stability of the eyebrow position with aging. This results from a physiological state of muscular compensation and may help explain the questionable results of eyebrow surgery.